Tracking the Market Performance of Companies That Integrate a Culture of Health and Safety: An Assessment of Corporate Health Achievement Award Applicants. Issue 1 (January 2016) - Fabius, Raymond; Loeppke, Ronald R.; Hohn, Todd; Fabius, Dan; Eisenberg, Barry; Konicki, Doris L.; Larson, Paul
Abstract : Objective: The aim of this study was to assess the hypothesis that stock market performance of companies achieving high scores on either health or safety in the Corporate Health Achievement Award (CHAA) process will be superior to average index performance. Methods: The stock market performance of portfolios of CHAA winners was examined under six different scenarios using simulation and past market performance in tests of association framed to inform the investor community. Results: CHAA portfolios out-performed the S&P average on all tests. Conclusions: This study adds to the growing evidence that a healthy and safe workforce correlates with a company's performance and its ability to provide positive returns to shareholders. It advances the idea that a proven set of health and safety metrics based on the CHAA evaluation process merits inclusion with existing measures for market valuation.